1277 Newly developed and redesigned key indicator methods for assessment of different physical workloads – key elements of the validation study. (24th April 2018) - Klussmann, A; Liebers, F; Brandstädt, F; Schust, M; Serafin, P; Schäfer, A; Gebhardt, H; Hartmann, B; Steinberg, U
Abstract : Introduction: The assessment of work tasks with physical workloads is crucial to estimate the work-related health risks of employees. Three key indicator methods (KIMs) are available for risk assessment regarding manual lifting, holding and carrying of loads, manual pulling and pushing, and manual handling operations. Three further KIMs regarding whole-body forces, awkward body postures and body movement have been developed de novo . The development of a combined method for mixed exposures is planned. All methods will be validated regarding face validity, reliability, convergent validity, criterion validity. Methods: A mixed-methods study was designed for the validation of KIMs. The following working hypotheses (WH) are tested: WH 1: The KIMs reflect adequately the construct to be measured (face validity). WH 2: No relevant deviations occur between different users using KIMs and assessing the same workplaces (reliability). WH 3: Assessing workplaces using the KIMs and other screening methods will result in no relevant differences (convergent validity). WH 4: It is assumed that employees at workplaces with high KIM risk scores show adverse health related outcomes more frequently than non-exposed workers (criterion validity). With this background a field study was conducted in companies of different sizes and branches in Germany as part of the joint project MEGAPHYS (multilevel risk assessment of physical workloads). Ethics and dissemination: The study was planned and conducted in accordance with the Declaration of Helsinki, the design was approved by ethics committees. We intend to publish validated KIMs in 2018. Acknowledgements/funding: The (further) development and validation of the KIMs is part of project MEGAPHYS funded by BAuA and the German Social Accident Insurance (DGUV). Further MEGAPHYS partners are Institute for Occupational Safety and Health of DGUV (IFA), Institute of Ergonomics at the Darmstadt University of Technology (IAD) and Leibniz Research Centre for Working Environment and Human Factors (IfADo).